2009
DOI: 10.1097/sle.0b013e3181bd94f8
|View full text |Cite
|
Sign up to set email alerts
|

Trocar Site Adhesions After Laparoscopic Surgery in Children

Abstract: Our results buttress the claim that the risk of adhesion formation after laparoscopic surgery in children is low. The reduction in the number of trocars used seems to further reduce this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A retrospective study conducted between 1998 and 2008 found that a reduction in the number of trocars reduces the risk of trocar site adhesions. Similarly, because the DILA technique eliminates one site of peritoneal invasion, it reduces the chance of adhesion . Furthermore, modification of 5‐mm port from the right iliac fossa to the umbilicus did not increase surgical difficulty; there was no difficulty in manipulating the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted between 1998 and 2008 found that a reduction in the number of trocars reduces the risk of trocar site adhesions. Similarly, because the DILA technique eliminates one site of peritoneal invasion, it reduces the chance of adhesion . Furthermore, modification of 5‐mm port from the right iliac fossa to the umbilicus did not increase surgical difficulty; there was no difficulty in manipulating the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest benefit of SILS appears to be the superior cosmetic result; this is an important issue for relatively young populations who are prone to developing Crohn's disease and requiring more surgeries. Moreover, the occurrence of adhesions following laparoscopic procedures is associated with the number of trocars used , and this reduced port surgery may contribute to a decrease in postoperative intestinal obstruction and surgical risk due to adhesion at reoperation.…”
Section: Discussionmentioning
confidence: 99%